Role of consumer satisfaction in mediating effect of product quality on repurchase intention - Sari, Dewa Ayu Taman; Giantari, I. G. A. K. (International research journal of management, IT and social sciences, 2020)
The purpose of this study is to explain the effect of product quality on consumer satisfaction and repurchase intention Berrybenka.com consumers in the city of Denpasar. The sample used was Berrybenka.com consumers in the city of Denpasar with a total of 105 respondents with a sample collection technique using purposive sampling. This research uses PLS (Partial Least Square) analysis technique. The results found that the quality of the product had a significant positive effect on repurchase intentions. Product quality has a significant positive effect on customer satisfaction. Consumer satisfaction has a significant positive effect on repurchase intentions. Consumer satisfaction acts as a partial mediating variable on the effect of the relationship of product quality on repurchase intentions. The implications of this study indicate that to increase the repurchase intention of its products, Berrybenka.com should need to pay attention to the factors of product quality and customer satisfaction. To maintain and increase market share, Berrybenka.com needs to maintain the quality of its products. Good product quality will increase customer satisfaction and encourage repurchase intentions of Berrybenka.com consumers in the future.